Influencia de los corredores económicos en la producción de limón de exportación en la región Piura - Soto Plasencia, Mercedes (2006)
This paper uses the approaches and concepts of competitive and comparative advantage modelsand the principles of economic corridors, including production chains, clusters and conglomerates,to analyze the potential for improved lime production in Peru’s northern regions for export to Asia Pacific markets. The first section discusses the relevance of adopting a strategy based oneconomic corridors as an efficient alternative to combine scale of production and efficient logisticscosts, in particular for the Sullana-Tambogrande-San Lorenzo-Ayabaca and Chulucanas-Morropon-Huancabamba corridors. The second section adopts a systemic view of agro-industrial competitiveness to identify the barriers to and ex ante conditions that have a positive impact onlime production, namely adoption of technologies, growers’ associations, access to financing,adoption of mechanized planting and harvesting techniques, and others.